2019
DOI: 10.22201/ib.20078706e.2019.90.2246
|View full text |Cite
|
Sign up to set email alerts
|

Specific habitat requirements and niche conservatism for nine species of the Mexican genus Thelocactus (Cactaceae)

Abstract: Specific habitat requirements and niche conservatism for nine species of the Mexican genus Thelocactus (Cactaceae) Requerimientos específicos de hábitat y conservación de nicho para nueve especies del género mexicano Thelocactus (Cactaceae)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 58 publications
1
3
0
Order By: Relevance
“…2) expands the southwestern limits of the known distribution of this species endemic to Mexico (GBIF 2021). In Aguascalientes, it is distribuited at the northeastern border of the state, in the Chihuahuan Desert biogeographic province (Morrone et al 2017), in microphyllous desert scrub (Siqueiros-Delgado et al 2017), habitat similar to the previously reported for all the members of the genus Thelocactus (Mosco 2019).…”
supporting
confidence: 77%
“…2) expands the southwestern limits of the known distribution of this species endemic to Mexico (GBIF 2021). In Aguascalientes, it is distribuited at the northeastern border of the state, in the Chihuahuan Desert biogeographic province (Morrone et al 2017), in microphyllous desert scrub (Siqueiros-Delgado et al 2017), habitat similar to the previously reported for all the members of the genus Thelocactus (Mosco 2019).…”
supporting
confidence: 77%
“…The role of temperature and precipitation as drivers of diversification and bioregionalization has long been recognized (e.g., Antonelli, 2017). For Cactaceae, temperature seems to be the most important factor to predict the species diversity in the Neotropics, which was also demonstrated for specific genera of cactus and other groups of species distributed in xeric landscapes (López, 2017;Gottlieb et al, 2019;Mosco, 2019;Aquino et al, 2021). The isothermality (diurnal range of temperatures per temperature seasonality) in arid and semiarid regions, including desertic areas, displays low oscillations between day and night, which seems to favor CAM photosynthetic metabolism and the reduction in evapotranspiration of Cactaceae (stomata remaining closed during the daytime; Mosco, 2019).…”
Section: 1predictor Variables Of Cactaceae Endemismmentioning
confidence: 99%
“…Another genus that shares a similar pattern with Epithelantha is Thelocactus Britton & Rose. Similar isothermal values imply that the habitat is subject to extreme temperature fluctuations (Mosco, 2019). Isothermality has also favored adaptive radiation events in Mammillaria (López, 2017), and together with precipitation seasonality, these variables have been involved in the differentiation of Stenocereus species (Alvarado-Sizzo et al, 2018).…”
Section: Influence Of Soil and Bioclimatic Variables On The Evolution Of Epithelanthamentioning
confidence: 98%